Cabozantinib and nivolumab as first-line treatment in advanced renal cell carcinoma. Issue 11 (2nd November 2021) - Vitale, Maria Giuseppa; Nasso, Cecilia; Oltrecolli, Marco; Baldessari, Cinzia; Fanelli, Martina; Dominici, Massimo; Sabbatini, Roberto
ABSTRACT: Introduction: In the last decade, there have been substantial changes in the management of metastatic renal cell carcinoma (mRCC) with combined regimens with immune checkpoint inhibitors (ICI) replacing targeted therapies. These combined regimens include the combination of cabozantinib plus nivolumab. Areas covered: Here, we provide an overview of clinical trials evaluating the combination of cabozantinib and nivolumab and the current clinical data on mechanism of action, pharmacokinetics, efficacy, and safety profile. Expert opinion: Dual immune checkpoint inhibition with nivolumab and ipilimumab as well as the combination of a vascular endothelial growth factor (VEGF) inhibitor and an immune checkpoint inhibitor have shown to improve outcomes in phase III trials in comparison to sunitinib (axitinib plus pembrolizumab, axitinib plus avelumab, bevacizumab plus atezolizumab, cabozantinib plus nivolumab, lenvatinib plus pembrolizumab). However, to date, there are no head-to-head trials comparing these new combination therapies and no biomarkers are available to guide the optimal choice of first line therapy.